Incremental direct and indirect costs of untreated vasomotor symptoms. Issue 3 (March 2015) - Sarrel, Philip; Portman, David; Lefebvre, Patrick; Lafeuille, Marie-Hélène; Grittner, Amanda Melina; Fortier, Jonathan; Gravel, Jonathan; Duh, Mei Sheng; Aupperle, Peter M.
Abstract: Objective: Most women with moderate to severe vasomotor symptoms (VMS) are untreated. This retrospective matched-cohort study aims to evaluate the healthcare resource utilization, work loss, and cost burden associated with untreated VMS. Methods: Health insurance claims (1999-2011) were used to match (1:1) women with untreated VMS with control women using propensity score. Healthcare resource utilization, work productivity loss (disability + medically related absenteeism), and associated costs were compared between cohorts. Results: During the 12-month follow-up, women with untreated VMS (n = 252, 273; mean age, 56 y) had significantly higher healthcare resource utilization than women in the control cohort: 82% higher for all-cause outpatient visits (95% CI, 81-83; P < 0.001) and 121% higher (95% CI, 118-124; P < 0.001) for VMS-related outpatient visits. Mean direct costs per patient per year were significantly higher for VMS women (direct cost difference, US1, 346; 95% CI, 1, 249-1, 449; P < 0.001). VMS women had 57% (95% CI, 51-63; P < 0.001) more indirect work productivity loss days than controls, corresponding to an incremental indirect cost per patient per year associated with untreated VMS of US770 (95% CI, 726-816; P < 0.001). Conclusions: This study shows that untreated VMS are associated with significantly higher frequency of outpatient visits and incremental direct and indirect costs. Abstract : Supplemental digital content is available in the text.